Evaluation of Probiotic Growth in Microenvironments Sculpted with Different Geometries - Otuka, Adriano J. G. [UNESP]; Moraes, Jonathas Q. R.; de Oliveira, Analú Barros [UNESP]; Fonseca, Eduardo J. S.; Fontana, Carla R. [UNESP]; Mendonca, Cleber R. (American Chemical Society (ACS), 2025)
Probiotics benefit their host, potentially exerting microbial balance by stimulating the increase in beneficial bacteria in the intestinal environment. Some studies have shown that specific probiotic strains can alleviate symptoms of medical conditions such as Alzheimer's, reduce the action of carcinogenic agents, and control various biomarkers in women in the first half of pregnancy. In this context, it is important to determine the fundamental aspects of probiotic growth to develop more efficient delivery mechanisms in pharmaceuticals or foods. Miniaturized biomimetic environments can be useful for that purpose. In this way, we manufactured biocompatible three-dimensional platforms using two-photon absorption polymerization to study the growth of a pool of bacteria composed of Lactobacillus acidophilus, Lactobacillus rhamnosus, Lactobacillus paracasei, and Bifidobacterium lactis, commonly used in commercial probiotics. The microstructures were fabricated using an acrylic resin employing 100 fs pulses from a Ti:sapphire laser. It was possible to manufacture biocompatible structures for probiotic development, demonstrating that microstructures serve as accelerators for bacterial growth. We evaluated the growth of bacteria in the environments over more than 36 h, giving all conditions for their development. Furthermore, it was observed that bacteria grow into structures with distinct geometries (circular or rectilinear) but tend to develop preferentially in protected environments with spacings on the order of 5 μm.